The Problem of the Image of a Modern Teacher in Social and Humanitarian Knowledge: Array - Zvekova, Victoria (Journal of Danubian Studies and Research, 2020)
This article discusses the most famous tools and methods of forming and developing the image of a modern teacher. The image is one of the main elements of management that contributes to increasing the efficiency of the organization. In addition, it is an instrument of influence on the public and individual consciousness, which needs constant monitoring. However, the image acts not only as a means of management, but also as an object of management. Therefore, starting from the moment of its formation, it is necessary to carry out purposeful continuous work on the image, while taking into account the characteristics of each target group. All this will help the modern teacher to correctly formulate and develop their image. After all, image is the key to success of a leader.